Strategi Pengembangan Industri Klaster Makanan Halal di Indonesia - Hariyono, Hariyono; Saniah, Iah; Nurcahyati, Meli (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The halal food cluster industry market in Indonesia is currently developing, but the potential of the cluster market has not been fully carried out optimally, so to maintain the quality and loyalty of food clusters in Indonesia is something that must be optimized so that Indonesia's halal food cluster can compete with other countries. This study aims to explain the strategy of developing the halal food cluster industry in MSMEs in Indonesia. This writing method uses qualitative research. Sunber primary and secondary data were obtained from literature studies. The type of data is qualitative data. Data collection techniques are carried out through webseite searches related to the halal industry. Data analysis techniques are descriptive analytical. According to Lady Yulia, at this time the halal industry really prioritizes and builds the halal product industry in the global market through business networks, thus the halal product industry will continue to develop and can increase the effectiveness of halal product development in Indonesia, therefore it is very important for community involvement in the process of developing halal product industry because it can optimize resources, In addition, it can also create a good communication climate between the government and the community.